Device Perfomance for CTS-Based Thin Film Solar Cell Using Scaps-1d Simulator - Fakhrul Md Islam; Mohammad Aminul Islam; Dilip Kumar Sarkar; Nadhrah Md Yatim (UMT Press, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)